PENGGUNAAN BUKU POP UP UNTUK MENINGKATKAN KEMAMPUAN PRESENTASI SISWA KELAS V SDN 42 MATARAM - Burhanuddin Burhanuddin (Asaatidzah, 2023)
A Good Practice (Best Practice) implementation of learning using Pop Up Book media in the learning of Islamic Religious Education and Characteristics, to help students improve their presentation skills about the results of discussions on the material The Beauty of Tarawih Prayers and Tadarus Al-Qur’an for Grade V Students of SDN 42 Mataram. After observing the teacher's activities, discussing and presenting the learning outcomes of 36 fifth grade students at SDN 42 Mataram using this media, classically these students have achieved an average classical score of 84.58 with a good success category.